Pension Systems and Financial Systems in Europe: A Comparison from the Point of View of Complementarity - Reinhard H. Schmidt; Marcel Tyrell (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2001)
At present, the question of how national pension or retirement payment systems should be organised is being hotly debated in various countries, and opinions vary widely as to what should be regarded as the optimal design for such systems. It appears to the authors of the present paper that in this entire discussion one aspect is largely overlooked: What relationships exist between the pension system and the financial system in a given country? As such relationships might prove to be important, the present paper investigates the following questions: (1) Are there differences between the national pension systems of three major European countries – Germany, France and the U.K. – and between the financial systems of these countries? (2) And if the existence of such differences can be demonstrated, is there a correspondence between the differences with respect to the various national pension systems and the differences as regards the countries' financial systems? (3) And if such a correspondence exists, is there any kind of interrelationship between the national financial and pension systems of the individual countries which goes beyond a mere correspondence? Looking mainly at two aspects – namely, risk allocation and the incentives to create human capital – the authors of this paper argue (1) that there are indeed considerable differences between the financial and pension systems of the three countries; (2) that in both Germany and the U.K. there are also systematic correspondences between the respective pension systems and financial systems and their economic characteristics, but that such a correspondence cannot be identified in the case of France; and (3) that these parallels are, in the final analysis, based on complementarities and are therefore likely to contribute to the efficiency of the German and the British systems. The paper concludes with a brief look at policy implications which the existence of, or the lack of, consistency between national pension systems and national financial systems might have.
urn:nbn:de:hebis:30-18451
Keywords: G10; G34; H55; P51; 330; Financial system; human capital formation; pension system; risk allocation; Altersvorsorge; Gesetzliche Rentenversicherung; Finanzsystem; Finanzsektor; Unternehmensfinanzierung; Corporate Governance; Vergleich; Deutschland; Großbritannien; Frankreich